(untitled) (REMUNOM, 2023)
The principle of insignificance is a relevant concept within the scope of criminal law, which suggests that minor or insignificant criminal conduct should be treated with leniency by the justice system, in order to avoid overloading the courts and disproportionate application of the law. Although the application of this principle is, ultimately, a judicial matter, there is much debate about the role of the police authority in the possible application of the principle of insignificance before the possible initiation of a criminal investigation. Furthermore, it is understood that the police authority has the duty to act to maintain order, due to the principle of obligation, however, the chance of police action encountering a visibly atypical occurrence and having to carry out the same procedures as a A typical crime raises the issue claimed below.